Modern criminal law essays in honour of GR Sullivan - Simester, A. P. (Hart, 2024)
"This book brings together leading scholars from the next generation of UK criminal lawyers to celebrate the work of GR Sullivan, Emeritus Professor at University College London, in the year of his retirement from writing Simester and Sullivan's Criminal Law: Theory and Doctrine. The contributors examine many of the areas in which GR (Bob) Sullivan's own writing has been influential, ranging from general doctrines such as causation and culpability, across specific offences like theft and fraud, through defences including necessity and insanity; before turning, finally, to matters affecting the criminal process, notably challenges to the doctrine of precedent in criminal law. Taken together, the essays are a powerful tribute to Bob's standing and influence upon modern criminal law. At the same time, individually they make sophisticated contributions to our understanding of some pressing issues in contemporary criminal law. The essays illustrate the increasing importance of theoretical argument in modern criminal law, as well as the manner in which doctrinal debates have become interwoven with arguments about criminalisation norms. The resulting collection is thus a tribute also to the character of modern academic criminal law, a character that Bob and the writers of his generation did so much to develop. " --